2021
DOI: 10.3390/app11199336
|View full text |Cite
|
Sign up to set email alerts
|

Polysorbate-Based Drug Formulations for Brain-Targeted Drug Delivery and Anticancer Therapy

Abstract: Polysorbates (PSs) are synthetic nonionic surfactants consisting of polyethoxy sorbitan fatty acid esters. PSs have been widely employed as emulsifiers and stabilizers in various drug formulations and food additives. Recently, various PS-based formulations have been developed for safe and efficient drug delivery. This review introduces the general features of PSs and PS-based drug carriers, summarizes recent progress in the development of PS-based drug formulations, and discusses the physicochemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 145 publications
2
13
0
Order By: Relevance
“…These nano-particles were coated with acacia and polysorbate 80 (P80) to form P80-Que@Se NC. P80 was used to enhance the permeability across BBB and acts as a pharmaceutical excipient that increases the aqueous solubility of Que, which is in good accordance with previously reported studies [ 105 , 106 ]. Results reported from in vitro analyses showed that P80-Que@Se had high water solubility compared to individual Que.…”
Section: Nano-delivery Systems Entrapping Que—new Approaches For Bioa...supporting
confidence: 87%
“…These nano-particles were coated with acacia and polysorbate 80 (P80) to form P80-Que@Se NC. P80 was used to enhance the permeability across BBB and acts as a pharmaceutical excipient that increases the aqueous solubility of Que, which is in good accordance with previously reported studies [ 105 , 106 ]. Results reported from in vitro analyses showed that P80-Que@Se had high water solubility compared to individual Que.…”
Section: Nano-delivery Systems Entrapping Que—new Approaches For Bioa...supporting
confidence: 87%
“…The type and concentration of surfactant, added in the aqueous phase, are parameters that must be taken in account, since, by decreasing the surface tension between the lipid phase and the aqueous phase, they influence the stability of the formulation. The choice of the surfactant fell on Tween ® 80 because, as reported in the literature, it is widely used in the formulation of ophthalmic preparations, and it is FDA-approved for ophthalmic applications [28]. In particular, the study by Leonardi et al, in which lipid carriers were prepared using different surfactants, showed that Tween ® 80 is particularly safe and welltolerated compared to other surfactants [29].…”
Section: Resultsmentioning
confidence: 99%
“…Tween 80 (Polysorbate 80) is a hydrophilic nonionic surfactant that is widely used for various drug products as an emulsifier, stabilizer, wetting agent, foaming agent, or dispersant [ 34 ]. By enhancing the permeability of phospholipid membranes, Tween 80 improves skin penetration for transdermal drug delivery [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%